Vulnerabilidade aquífera e risco potencial à poluição das águas subterrâneas ao uso dos agrotóxicos no Município de Limoeiro do Norte - Ceará - Tavares, Tércio Dantas (2023)
The municipality of Limoeiro do Norte - Ceará is located in the Mesoregion of Jaguaribe, Microregion of Baixo Jaguaribe in the Vale do Jaguaribe, comprising one of the most important areas of irrigated fruit growing in the State of Ceará. Most fruit growers in the region cultivate conventionally, which includes the use of pesticides without agronomic prescriptions and in disagreement with the recommendations recommended by the manufacturer. The indiscriminate use of these products, along the timeline, can cause the contamination of local groundwater, the intensity and risk being certain due to the characteristics of the environment and the contaminant itself. This Dissertation aims to evaluate the vulnerability and potential risk of groundwater contamination by irrigated agriculture activities in Limoeiro do Norte. The geoenvironmental data and information were initiated in technical works published in national and international magazines and periodicals, reports and books. The analysis of aquifer vulnerability to anthropogenic risk was carried out using the criteria of the Environmental Protection Agency (EPA), the GOD and GUSS methods. These criteria are based on physical-chemical properties of the active principles of each pesticide and hydrogeological parameters. According to the Köppen climate classification, the climate of Limoeiro do Norte is of the BSW'h' type, very hot, semi-arid with a rainy season late to autumn and has two very distinct seasons: the dry and the rainy, the latter occurring between the months of February to May. Atmospheric precipitation is observed from January to May, oscillating, on average, from 638.58 to 813.26 mm/year. As main geomorphological units are present the Chapada do Apodi, which extends to the state of Rio Grande do Norte, the Alluvial Plain, and the Sertaneja Depression. There are vast alluvial patches and lithologically there are the limestones of the Jandaíra Formation, which form the Jandaíra Karst Aquifer, overlapping the sandstones of the Açu Aquifer where all rest on the crystalline basement, forming the edge of the Potiguar Basin. Among the 29 pesticides used in the area, 11 are classified as insecticides (37.9%), followed by acaricides (20.7%). The high rate of insecticide application in crops is justified by the fact that these substances are widely used to control insects and pests, mainly in corn and bean crops in the region. The vulnerability index calculated by the GOD method for the area ranged from Moderate to High, reaching Extreme vulnerability. The areas where the highest rates occur are related to the Alluvial Aquifers, Açu and Jandaíra (karstic). In this study, the main products applied to irrigated crops in the municipality of Limoeiro do Norte were evaluated through an in situ survey. The 134,345 liters of different pesticides, with different toxicological degrees, in use in the region, associated with a shallow water table, freatic, and a karst environment with high porosity and permeability, in addition to ―sinks‖ in the karst, confer a high risk of contamination of the groundwater. By comparing the proposed models, some pesticides showed a greater potential for contamination in groundwater, requiring constant monitoring of the levels of these residues. Finally, a proposal for a solid phase pre-extraction (SPE) methodology for the analysis of the considered pesticides is presented.